2013
DOI: 10.1111/1753-6405.12079
|View full text |Cite
|
Sign up to set email alerts
|

The Australian Recommended Food Score did not predict weight gain in middle‐aged Australian women during six years of follow‐up

Abstract: This lack of association may be due to limitations related to AFRS, or may be a false negative finding. Further research is warranted to evaluate the impact of promoting optimal diet quality on weight gain prospectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…A longitudinal study, conducted in an American middle-aged population, demonstrated that those who achieved the highest score on the DQI had a smaller weight gain (3 pounds) than those who achieved the lowest DQI score (5–8 pounds) during eight years of followup [7]. In contrast, we have previously demonstrated that overall diet quality measured using the ARFS did not predict weight gain in a sub-sample of middle-aged women from the ALSWH [8]. …”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study, conducted in an American middle-aged population, demonstrated that those who achieved the highest score on the DQI had a smaller weight gain (3 pounds) than those who achieved the lowest DQI score (5–8 pounds) during eight years of followup [7]. In contrast, we have previously demonstrated that overall diet quality measured using the ARFS did not predict weight gain in a sub-sample of middle-aged women from the ALSWH [8]. …”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review found an association between poor diet quality and weight gain in adults, with 8 of the 10 studies that examined women only, having a significant inverse association between poor diet quality and weight gain. In a recent sub‐analysis of 48‐ to 56‐ year‐old women from the ALSWH, diet quality was not associated with six‐year weight change (β = 0.016; P = 0.08) as measured by the Australian Recommended Food Score . More attention should be focused on determining the association between diet quality, energy intake and adverse health outcomes in weight gain prevention studies because of the potential confounder of energy misreporting.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent sub-analysis of 48-to 56-year-old women from the ALSWH, diet quality was not associated with six-year weight change (β = 0.016; P = 0.08) as measured by the Australian Recommended Food Score. 30 More attention should be focused on determining the association between diet quality, energy intake and adverse health outcomes in weight gain prevention studies because of the potential confounder of energy misreporting.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that used this tool described better self-reported health status, higher intakes of key nutrients, and lower intakes of total fat and saturated fat in subjects among the highest quintile of Australian Recommended Food score (ARFS), compared to those in the lowest quintile. 110 Therefore, ARFS described nutrition's impact on health based on dietary patterns rather than on single nutrients intake. Such characteristic is particularly appealing for intervention studies, where changes in dietary patterns and food groups can be assessed and linked to health outcomes.…”
Section: Key Region Componentsmentioning
confidence: 99%
“…105 The ARFS has been recently validated with a middle-aged cohort in the Australian Longitudinal Study on Women's Health. 108,110 The calculation in this score was based on regular consumption of FFQ items that are in line with Australian dietary guidelines. 109,264 The method included seven sub-scales with scores ranging from 0-74.…”
Section: Dietmentioning
confidence: 99%